Norman to Early Plantagenet Consorts Power, Influence, and Dynasty - Norrie, Aidan; Harris, Carolyn; Laynesmith, J.L.; Messer, Danna R.; Woodacre, Elena (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This collection of short analytical biographies of medieval English queens from Matilda of Flanders to Margaret of France-and prefaced with an important overview of pre-Norman queens-is a treasure-trove of information on these significantly under-valued and under-studied subjects. As we continue to reassess the role and position of women in all walks of medieval life, we should also demand that queens be included in studies of politics, culture, and society in medieval realms, not just as mothers of kings but as actors in their own right. This volume, and the series in which it is included, goes far in showing us the ways in which these historical figures should be rightfully inserted into the records of the reigns of their husbands and sons." -Linda E. Mitchell, University of Missouri-Kansas City, USA This book examines the emergence of the queen consort in medieval England, beginning with the pre-Conquest era and ending with death of Margaret ofFrance, second wife of Edward I, in 1307. Though many of the figures in this volumes are well known, such as Eleanor of Aquitaine and Eleanor of Castille, the chapters here are unique in the equal consideration given to the tenures of the lesser known consorts, including: Adeliza of Louvain, second wife of Henry I; Margaret of France, wife of Henry the Young King; and even Isabella of Gloucester, the first wife of King John. These innovative and thematic biographies highlight the evolution of the office of the queen and the visible roles that consorts played, which were integral to the creation of the identity of early English monarchy. This volume and its companions reveal the changing nature of English consortship from the Norman Conquest to today. Aidan Norrie is Lecturer in History and Programme Leader at the University Campus North Lincolnshire, UK, and the Managing Editor of The London Journal. Carolyn Harris is Instructor in History at the University of Toronto School of Continuing Studies, Canada, and a regular royal commentator in Canadian media. J.L. Laynesmith is Visiting Research Fellow in Medieval Studies at the University of Reading, UK. Danna R. Messer is Senior Acquisitions Editor at Arc Humanities Press, and the Executive Editor of The Encyclopedia of the Global Middle Ages. Elena Woodacre is Reader in Renaissance History at the University of Winchester, UK, Editor-in-Chief of the Royal Studies Journal, and the founder of the Royal Studies Network.
Chapter 1: The Emergence of the Queen Consort in England, 1066-1307: Power, Influence, Dynasty -- Chapter 2: Identifying Queenship in Pre-Conquest England -- Chapter 3: Mathilda of Flanders: Innovator -- Chapter 4: Matilda of Scotland: Peacemaker and Perfect Princess -- Chapter 5: Adeliza of Louvain: Patron -- Chapter 6: Matilda of Boulogne: Indispensable Partner -- Chapter 7: Eleanor of Aquitaine: The Art of Governing -- Chapter 8: Margaret of France: Conciliator Queen of England and Hungary -- Chapter 9: Berengaria of Navarre: Overshadowed Consort -- Chapter 10: Isabella of Gloucester: Heiress, Lord, Forgotten Consort -- Chapter 11: Isabella of Angoulême: The Vanished Queen? -- Chapter 12: Eleanor of Provence: Caring Consort and Controversial Queen -- Chapter 13: Eleanor of Castile: A Consort of Contradictions -- Chapter 14: Margaret of France: Enigmatic Consort -- Chapter 15: Epilogue: Shifting Sands and Changing Lands.
Keywords: Great Britain -- History; Europe -- History -- 476-1492.; Imperialism; Sex; History of Britain and Ireland; History of Medieval Europe; Imperialism and Colonialism; Gender Studies